Hepatitis B Virus Adaptation to the CD8+ T Cell Response: Consequences for Host and Pathogen - Lumley, Sheila F.; McNaughton, Anna L.; Klenerman, Paul; Lythgoe, Katrina A.; Matthews, Philippa C. (Frontiers in Immunology, 2018)
Chronic viral hepatitis infections are a major public health concern, with an estimated 290 million individuals infected with hepatitis B virus (HBV) globally. This virus has been a passenger in human populations for 30,000 years, and remains highly prevalent in some settings. In order for this endemic pathogen to persist, viral adaptation to host immune responses is pre-requisite. Here we focus on the interplay between HBV infection and the CD8+ T cell response. We present the evidence that CD8+ T cells play an important role in control of chronic HBV infection and that the selective pressure imposed on HBV through evasion of these immune responses can potentially influence viral diversity, chronicity, and the outcome of infection. Understanding the nature and mechanisms of HBV evolution and persistence could shed light on differential disease outcomes, including cirrhosis and hepatocellular carcinoma, and help reach the goal of global HBV elimination by guiding the design of new strategies, including vaccines and therapeutics.